2019
DOI: 10.1002/ccd.28573
|View full text |Cite
|
Sign up to set email alerts
|

“Between a rock and the mitral valve space”: Transcatheter mitral valve‐in‐valve implantation for paravalvular leak and refractory hemolysis complicated by circumflex coronary occlusion

Abstract: Transcatheter mitral valve implantation (TMVI) is an emerging field in structural cardiology. A particularly difficult group to treat is high‐risk patients requiring valve in mitral annular calcification (ViMAC) intervention, with overall poor procedural success and outcomes in recent registries. This case highlights an unusual complication of paravalvular regurgitation (PVL) through the uncovered stent frame of a balloon expandable transcatheter heart valve (THV) on the left ventricular side of the prosthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Since the first presentation of this tool, numerous studies have demonstrated its clinical usage including for implantation in bicuspid aortic valves, [71][72][73] and the use of TAVI in the mitral location with native calcified valves 74,75 and inside a failed bioprosthetic valve. 76 Use of the FEops HEARTguide has also been expanded to additional TAVI devices, 77 device optimization, 78 and also for procedural recommendations based on additional possible complications, such as conduction abnormalities. 79 From a hemodynamic perspective, the most important capability of this tool is obviously calculation of PVL (Figure 4), which demonstrated good predictions in a clinical study of 60 patients.…”
Section: Patient-specific Pre-procedural Planning Based On Numerical mentioning
confidence: 99%
“…Since the first presentation of this tool, numerous studies have demonstrated its clinical usage including for implantation in bicuspid aortic valves, [71][72][73] and the use of TAVI in the mitral location with native calcified valves 74,75 and inside a failed bioprosthetic valve. 76 Use of the FEops HEARTguide has also been expanded to additional TAVI devices, 77 device optimization, 78 and also for procedural recommendations based on additional possible complications, such as conduction abnormalities. 79 From a hemodynamic perspective, the most important capability of this tool is obviously calculation of PVL (Figure 4), which demonstrated good predictions in a clinical study of 60 patients.…”
Section: Patient-specific Pre-procedural Planning Based On Numerical mentioning
confidence: 99%